2021
DOI: 10.1016/j.eclinm.2020.100663
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment optimization with pulmonary rehabilitation in lung cancer: Making the inoperable patients operable

Abstract: Background Anatomical lung resection offers the best prospect of long-term survival in patients with non-small cell lung cancer (NSCLC). However, some patients with significant dyspnoea, impaired performance status (PS), borderline or poor pulmonary function are considered inoperable and instead referred for radiotherapy, chemotherapy or palliative care. The aims of the study were to determine whether pre-operative pulmonary physiotherapy (Prehab), by improving clinical parameters, (i) makes patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…When comparing program type, the improvement in six-minute walk distance was only significant for rehab ( n = 7, WMD = 57 m, 95% CI = 29 to 85, p < 0.001, I 2 = 96%) ( 20 , 22 , 27 , 35 , 40 , 43 , 44 ) and not for prehab ( n = 3, WMD = 25 m, 95% CI = −16 to 67, p = 0.236, I 2 = 11%) ( 20 , 28 ) but was not statistically different between types ( p = 0.211). For treatment timing, the improvement was significant only among programs with participants exclusively post-treatment ( n = 7, WMD = 50 m, 95% CI = 18 to 81, p = 0.002, I 2 = 97%) ( 22 , 24 , 29 , 30 , 42 , 45 ) and was only a trend among programs that allowed patients on active treatment with surgery, chemotherapy, or radiation ( n = 3, WMD = 41 m, 95% CI = −8 to 90, p = 0.100, I 2 = 76%) ( 22 , 24 , 37 ) but did not differ between subgroups ( p = 0.765). Retrospective studies had larger improvements in six-minute walk distance ( n = 5, WMD = 70 m, 95% CI = 39 to 101, p < 0.001, I 2 = 97%) ( 24 , 29 , 37 , 42 , 46 ) than prospective ( n = 5, WMD = 25 m, 95% CI = −5 to 56, p = 0.107, I 2 = 66%) ( p = 0.042 between groups).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing program type, the improvement in six-minute walk distance was only significant for rehab ( n = 7, WMD = 57 m, 95% CI = 29 to 85, p < 0.001, I 2 = 96%) ( 20 , 22 , 27 , 35 , 40 , 43 , 44 ) and not for prehab ( n = 3, WMD = 25 m, 95% CI = −16 to 67, p = 0.236, I 2 = 11%) ( 20 , 28 ) but was not statistically different between types ( p = 0.211). For treatment timing, the improvement was significant only among programs with participants exclusively post-treatment ( n = 7, WMD = 50 m, 95% CI = 18 to 81, p = 0.002, I 2 = 97%) ( 22 , 24 , 29 , 30 , 42 , 45 ) and was only a trend among programs that allowed patients on active treatment with surgery, chemotherapy, or radiation ( n = 3, WMD = 41 m, 95% CI = −8 to 90, p = 0.100, I 2 = 76%) ( 22 , 24 , 37 ) but did not differ between subgroups ( p = 0.765). Retrospective studies had larger improvements in six-minute walk distance ( n = 5, WMD = 70 m, 95% CI = 39 to 101, p < 0.001, I 2 = 97%) ( 24 , 29 , 37 , 42 , 46 ) than prospective ( n = 5, WMD = 25 m, 95% CI = −5 to 56, p = 0.107, I 2 = 66%) ( p = 0.042 between groups).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies with n = 680 participants among 10 different programs evaluated change in six-minute walk test distance ( 22 , 24 , 29 , 30 , 37 , 42 , 45 , 46 ). Including all programs, pre/rehabilitation improved six-minute walk distance by 47 meters (95% CI = 23 to 71, SMD = 0.78, p < 0.001, I 2 = 96%; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Finland, an increase in resection rate over time, mainly due to inclusion of higher risk patients, resulted in fewer complications and shorter hospital stays while increasing recurrence-free 5-year survival from 64.0% to 76.8%. 14 Goldsmith et al 15 demonstrated that introduction of a prehabilitation programme to a surgical unit was associated with improvement in dyspnoea scores, PS, level of activity and frailty, particularly in high-risk patients. Prehabilitation facilitated resection in previously inoperable patients without increases in complications, length of hospital stay or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Prehabilitation facilitated resection in previously inoperable patients without increases in complications, length of hospital stay or mortality. 15 …”
Section: Discussionmentioning
confidence: 99%